ANALISIS STRATEGI BERSAING PRODUK PRIVATE BRAND DALAM BISNIS RITEL MODERN - Fransiska Fortunata (Universitas Trunojoyo Madura, 2014)
The growth of modern retail business in Indonesia influence the competition among retailer. The number of modern retail which increasing each year marks the rapid growth of modern retail business. The entry of foreign retailers is also a promoter factor increasing the retail business in Indonesia. Indonesia is the target for retailers because of the high purchasing power of its people. To be competitive in the retail business, retailer create private brand products. Private brand comes with a cheaper price than other brands. But for some consumers, low prices creates the perception of low quality. Consumers still unfamiliar with the private brand products and still considers that the national brand products or other brands that are well known to have better quality. This article discusses the most appropriate strategy of the attributes of private brand products to compete with national brands / other brands. The conclusion of this discussion is to set the attributes of packaging as the most appropriate attributes to be used as a competition strategy. This is because the attributes of the packaging is considered to represent the quality of the product and increase purchase intention.